Is interpretation bias for threat content specific to youth anxiety symptoms/diagnoses? A systematic review and meta-analysis. - Subar, Anni R.; Humphrey, Kaeli; Rozenman, Michelle (European Child & Adolescent Psychiatry, 2022)
Anxiety is the most common mental health problem in youth. Numerous studies have identified that youth anxiety is associated with interpretation bias or the attribution of threatening meaning to ambiguity. Interpretation bias has been proposed as a mechanism underlying the development and maintenance of pediatric anxiety. Theoretically, interpretation bias should be content-specific to individual youth anxiety symptom domains. However, extant studies have reported conflicting findings of whether interpretation bias is indeed content specific to youth anxiety symptoms or diagnoses. The present meta-analysis aimed to synthesize the literature and answer the question: is the relationship between interpretation bias and anxiety content specific? Search of PubMed and PsycINFO databases from January 1, 1960 through May 28, 2019 yielded 9967 citations, of which 19 studies with 20 comparisons and 2976 participants met eligibility criteria. Meta-analysis with random effects models was conducted to examine an overall effect (Pearson r) between anxiety domain and content-specific interpretation bias in single sample studies, and an overall effect size difference (Cohen's d) in studies comparing anxious to non-anxious youth. Results support a content specific correlation between interpretation bias and anxiety symptom domain in single sample studies (r = 0.18, p = 0.03). However, it is currently undetermined whether this relationship holds in studies that compare the relationship between content-specific interpretation bias and anxiety in anxious versus non-anxious youth. A variety of methodologic considerations across studies are discussed, with implications for further investigation of interpretation bias and youth anxiety.